A Fully Biodegradable Ferroelectric Skin Sensor from Edible Porcine Skin Gelatine. Issue 13 (7th May 2021) - Ghosh, Sujoy Kumar; Park, Jonghwa; Na, Sangyun; Kim, Minsoo P.; Ko, Hyunhyub
Abstract: High‐performance biodegradable electronic devices are being investigated to address the global electronic waste problem. In this work, a fully biodegradable ferroelectric nanogenerator‐driven skin sensor with ultrasensitive bimodal sensing capability based on edible porcine skin gelatine is demonstrated. The microstructure and molecular engineering of gelatine induces polarization confinement that gives rise the ferroelectric properties, resulting in a piezoelectric coefficient ( d 33 ) of ≈24 pC N −1 and pyroelectric coefficient of ≈13 µC m −2 K −1, which are 6 and 11.8 times higher, respectively, than those of the conventional planar gelatine. The ferroelectric gelatine skin sensor has exceptionally high pressure sensitivity (≈41 mV Pa −1 ) and the lowest detection limit of pressure (≈0.005 Pa) and temperature (≈0.04 K) ever reported for ferroelectric sensors. In proof‐of‐concept tests, this device is able to sense the spatially resolved pressure, temperature, and surface texture of an unknown object, demonstrating potential for robotic skins and wearable electronics with zero waste footprint. Abstract : Fully transient ferroelectric electronic skin (e‐skin) is demonstrated based on edible porcine skin gelatine. The interlocked molecular engineering induces ferroelectricity in gelatine. The e‐skin detects and discriminates the lowest possible resolution of pressure and temperature ever reported for ferroelectric sensors. In proof‐of‐concept tests, the potential applications towards robotic skins and wearable electronics are demonstrated with zero waste footprint.